2022
DOI: 10.5664/jcsm.9800
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea syndrome as a rare presentation in a young girl with a central nervous system tumor

Abstract: Sleep related breathing disorders (SRBDs) are a common problem in infancy and childhood. The most common type of SRBD in this age group is obstructive sleep apnea syndrome (OSAS), generally caused by factors affecting airway patency, such as tonsillar hypertrophy or obesity. However, in adults OSAS can also be caused by processes affecting the brainstem, such as central nervous system tumors. This report describes a 2-year-old girl who presented with symptoms of snoring, restless sleep, repeated night-time wak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…CSA is rare in the paediatric population,6 although CSA has been rarely reported as a presenting feature of CNS tumours in this age group 7–9. It is unclear whether a tumour diagnosis would have been made in our patient if only obstructive sleep apnoea (OSA) was detected during the sleep study, although OSA has been reported as a presenting feature of a brain tumour in a toddler 10…”
Section: Descriptionmentioning
confidence: 84%
See 1 more Smart Citation
“…CSA is rare in the paediatric population,6 although CSA has been rarely reported as a presenting feature of CNS tumours in this age group 7–9. It is unclear whether a tumour diagnosis would have been made in our patient if only obstructive sleep apnoea (OSA) was detected during the sleep study, although OSA has been reported as a presenting feature of a brain tumour in a toddler 10…”
Section: Descriptionmentioning
confidence: 84%
“…[7][8][9] It is unclear whether a tumour diagnosis would have been made in our patient if only obstructive sleep apnoea (OSA) was detected during the sleep study, although OSA has been reported as a presenting feature of a brain tumour in a toddler. 10 The CNS neoplasms in the adult and paediatric cases presenting with apnoea were likely impairing the brainstem neuronal network. Tumours involving the posterior fossa may influence central chemoreceptors and pontine and medullary respiratory groups, consequently producing respiration abnormalities.…”
Section: Descriptionmentioning
confidence: 99%